2021
DOI: 10.3389/fnins.2021.657576
|View full text |Cite
|
Sign up to set email alerts
|

Altered Effective Connectivity of Children and Young Adults With Unilateral Amblyopia: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: The altered functional connectivity (FC) in amblyopia has been investigated by many studies, but the specific causality of brain connectivity needs to be explored further to understand the brain activity of amblyopia. We investigated whether the effective connectivity (EC) of children and young adults with amblyopia was altered. The subjects included 16 children and young adults with left eye amblyopia and 17 healthy controls (HCs). The abnormalities between the left/right primary visual cortex (PVC) and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“…The study suggests that children with amblyopia exhibit damage to V1, and there is a correlation between the left middle frontal gyrus, left inferior frontal gyrus, and BA17, hinting at a potential neural mechanism contributing to anisometropic amblyopia. In contrast to prior research [9‒12], our study observed an improved RSFC between the left posterior central gyrus of the anisometropic amblyopia group and BA17. This suggests that individuals can adapt to gather information from their surroundings through multiple sensory channels and senses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The study suggests that children with amblyopia exhibit damage to V1, and there is a correlation between the left middle frontal gyrus, left inferior frontal gyrus, and BA17, hinting at a potential neural mechanism contributing to anisometropic amblyopia. In contrast to prior research [9‒12], our study observed an improved RSFC between the left posterior central gyrus of the anisometropic amblyopia group and BA17. This suggests that individuals can adapt to gather information from their surroundings through multiple sensory channels and senses.…”
Section: Discussioncontrasting
confidence: 99%
“…Rs-fMRI studies have shown that brain dysfunction in amblyopic children extends beyond the occipital visual cortex. Abnormal spontaneous activity has been observed in the angular gyrus [9] and cingulate gyrus [10] of amblyopic patients. Wang et al [11] reported that compensations for amblyopia that are reflected in enhanced spontaneous brain function have been reported in the early visual cortices in the resting state, as well as reduced functional connectivity in the dorsal pathway and structural connections in the ventral pathway in both anisometropic amblyopia and strabismic amblyopia patients.…”
Section: Introductionmentioning
confidence: 99%
“…After 8 wk of treatment in the present study, the fALFF values of the left posterior cingulate gyrus, left precuneus, left middle occipital gyrus, and left inferior occipital gyrus were significantly lower in the acupuncture group than in the control group. In contrast, the fALFF values of the right inferior frontal gyrus, right insula, and right hippocampus in the acupuncture group were higher than those in the control group[ 14 , 15 ]. These results suggest that the combined use of acupuncture at ghost points and fluoxetine has a greater effect on the regulation of neurological function compared to fluoxetine alone when used in patients with mild to moderate depression[ 16 ].…”
Section: Discussionmentioning
confidence: 91%
“…The morpho-functional impairment of the lateral geniculate nucleus and visual cortex induced by amblyopia have been widely described [ 1 , 2 ] and recently supported by functional magnetic resonance imaging studies [ 3 ], however, the effects on retinal structures are still a debatable issue. Many studies, based on tomographic evaluation of macula and optic nerve in anisometropic/strabismic patients, reported substantially immature retinal architecture with increased retinal thickness and/or retinal nerve fiber layers (RNFL), reduced pit depth and frequent absence of the bulge of the foveal ellipsoidal zone [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%